Avoiding the danger that stop smoking services may exacerbate health inequalities: building equity into performance assessment - Low Anne; Unsworth Louise; Low Allan; Miller Iain (BMC, 2007)
Abstract Background The UK is the only developed country to have established a nation-wide stop smoking treatment service. Apart from addressing tobacco dependence, which is the leading preventable cause of ill health and premature death, smoking cessation has been identified by the UK department of health as a service priority for reducing gaps in health between disadvantaged groups and the country as a whole. However smoking cessation tends to be more successful among affluent than disadvantaged groups. This means that for stop smoking services there is a trade-off to be had in terms of maximising the number of quitters and reducing socioeconomic inequalities in smoking prevalence. Current performance targets for the national stop smoking services in the UK are set only in terms of numbers of quitters, which does not encourage the adoption of strategies to reduce socioeconomic inequalities in smoking prevalence. Discussion This paper proposes an assessment framework, which allows the two dimensions of overall reduction in smoking prevalence and reductions of inequalities in smoking prevalence to be assessed together. The framework is used to assess the performance over time of a stop smoking service in Derwentside, a former Primary Care Trust in the North East of England, both in terms of meeting targets for the overall number of quitters and in terms of reducing socioeconomic inequalities in smoking prevalence. The example demonstrates how the proposed assessment framework can be applied in practice given existing records kept by stop smoking services in England and the available information on smoking prevalence at small area level. For Derwentside it is shown that although service expansion was successful in increasing the overall number of quitters, the service continued to exacerbate inequality in smoking prevalence between deprived and affluent wards. Summary The Secretary of State for Health in the UK has warned about the dangers of health promotion services and messages being taken up more readily by the better-off, thus exacerbating health inequalities. Because smokers from affluent backgrounds are more successful at quitting than those living in deprived circumstances, it is important to build an equity element into the monitoring of individual stop smoking services. Otherwise the danger highlighted by the Secretary of State for Health will go undetected and unaddressed.